A phase-field model without artificial curvature effect for the crystal growth simulation. (April 2023) - Li, Yibao; Yu, Qian; Ham, Seokjun; Kwak, Soobin; Lee, Chaeyoung; Kim, Junseok
Highlights: A phase-field model without artificial curvature effect is proposed. The proposed model allows a fast dendritic growth. 2D and 3D computational simulations are presented. Abstract: In this study, we present a novel phase-field model without artificial curvature effect for the crystal growth simulation. Most phase-field models for dendritic growth are based on the anisotropic Allen–Cahn (AC) equation which models anti-phase domain coarsening in a binary alloy. However, the AC equation intrinsically contains the motion by mean curvature term, i.e., curvature flow, which may have effect on the phases transition. In this work, we remove the artificial curvature effect and propose a novel phase-field model without artificial curvature effect for the dendritic growth simulation. Both two- and three-dimensional numerical tests show that, in the case of the new phase-field model, dendritic growth develops faster than the conventional phase-field model because of the absence of artificial motion by mean curvature effect. In addition, we show that the proposed model has applicability to polycrystal growth.